Body Image Perception of Obese Individuals Monitored at the Endocrinology Clinic - Bonamich, Beatriz Dal Santo Francisco; Santos, Rafael Bonamichi dos; Amigo, Veruska Lastoria (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Evaluate body self-perception of obese patients monitored in an endocrinology clinic. Method: Cross-sectional study, with data obtained via interviews from fifty obese patients receiving treatment at the Endocrinology Clinic. We used a questionnaire asking about personal characteristics, comorbidities, medication, daily habits, and the calculation of Body Mass Index (BMI) for the classification of obesity according to sample variables defined by Cole et al. Body image was determined using the silhouette scale. Results: predominance of females with an association of obesity to other comorbidities such as diabetes mellitus, dyslipidemia, and arterial hypertension. In 44% of patients, the predominant behavioral profile was anxiety. The cause attributed to weight gain in 22% of cases was pregnancy, and emotional problems in 44.4%. Currently, 44% of patients assessed in this study are using adjuvant medication for weight loss, with sibutramine prescribed in 24% of cases. All these patients received relevant nutritional guidance. 40% of patients undertake physical activity. The main motivation for weight loss was health (48%). We can see that there is a significant variability in the distortion of body image, mainly with women, whereby 51.1% believe that their BMI is 2.5 points below the real level. In terms of intention, 40% wished to lose 5 points on the BMI, with the majority still classifying themselves as overweight even with this level. Conclusion: This study showed a distortion of body image, especially amongst women, demonstrating that they idealize an image less obese than what they really show themselves to be.